The effects of process conditions on the plasma characteristic in radio-frequency capacitively coupled SiH_4/NH_3/N_2 plasmas： Two-dimensional simulations - 刘相梅 宋远红 姜巍 易林 (中国物理B：英文版, 2013)
A two-dimensional （2D） fluid model is presented to study the behavior of silicon plasma mixed with SiH4 , N2 , and NH3 in a radio-frequency capacitively coupled plasma （CCP） reactor. The plasma–wall interaction （including the deposition） is modeled by using surface reaction coefficients. In the present paper we try to identify, by numerical simulations, the effect of variations of the process parameters on the plasma properties. It is found from our simulations that by increasing the gas pressure and the discharge gap, the electron density profile shape changes continuously from an edge-high to a center-high, thus the thin films become more uniform. Moreover, as the N2 /NH3 ratio increases from 6/13 to 10/9, the hydrogen content can be significantly decreased, without decreasing the electron density significantly.